A history of modernist literature - Gasiorek, Andrzej 1960- (Chichester, West Sussex, UK Wiley Blackwell, 2015)
"A History of Modernist Literature offers a critical overview of modernism in England from the 1890s to the Second World War"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Modernism (Literature) -- England